Dancing with dementia : my story of living positively with dementia - Bryden, Christine, 1949- (Jessica Kingsley, 2005)
Christine Bryden was a top civil servant and single mother of three children when she was diagnosed with dementia at the age of 46. Since then she has gone on to challenge almost every stereotype of people with dementia by campaigning for self-advocacy, writing articles and speaking at national conferences. This book is a vivid account of the author's experiences of living with dementia, exploring the effects of memory problems, loss of independence, difficulties in communication and the exhaustion of coping with simple tasks. She describes how, with the support of her husband Paul, she contin.